Character Based Holistic Education Management In SDIT An Nahl Guguak Limapuluh Kota - Ahmad, Zakaria; Agustina, Agustina (Mudir : Jurnal Manajemen Pendidikan, 2023)
A Character-Based Holistic Education (PHBK) is an educational pattern that elaborates on all aspects of human life, not only focusing on the development of intellectual abilities but also on other comprehensive and balanced multiple intelligence abilities through the application of the nine character pillars. The purpose of this study was to describe the planning, implementation and evaluation of character-based holistic education at SDIT An Nahl Guguak, Lima Puluh Kota Regency. This is a qualitative research study that uses a case study approach. Researchers directly as the main instrument by using interview guidelines and observation guidelines as supporting instruments. The results showed that, 1) Planning was carried out through meetings and discussions between the principal and the PHBK Team. There are several stages of planning carried out by the team, namely setting priorities, setting goals, making stages of action and handing over responsibilities. 2) The implementation of PHBK is carried out with two methods, namely specifically those carried out 20 minutes before starting the learning and integrated methods that are incorporated in the theme learning. 3) PHBK evaluation is carried out under direct control by the principal through weekly evaluation meetings, giving recommendations to parents and collecting portfolios from each child.